2016
DOI: 10.1097/jsm.0000000000000208
|View full text |Cite
|
Sign up to set email alerts
|

Return to Learning After a Concussion and Compliance With Recommendations for Cognitive Rest

Abstract: Ensuring that schools have policies established for a student's return to learning, having specific guidelines to provide an individualized approach to return to learning based on postconcussion signs/symptoms, training school nurses in the recognition and management of concussions, and involving school nurses in the re-entry process are identified areas for improvement. Schools in the United States should be aware of these recommendations to guide a student's postconcussion graduated academic re-entry process. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…Students in our study reported the most helpful accommodations to be engaging in cognitive and physical rest and having more time to complete work or a reduced workload. These findings are in agreement with a previous questionnaire-based study that found that 87% of concussed students were excused from physical activity, 87% received extensions on assignments, 84% were allowed excused absences, 84% received rest periods, 75% were able to postpone tests, 74% received extended testing time, 73% were permitted a reduced workload and 64% received accommodation for light and noise [31]. Taken together, the results of this pilot study have helped contribute to the development of an individually tailored return to learn (RTL) program at our tertiary pediatric concussion program, however future work is needed to evaluate the benefit of this RTL program in optimizing academic performance and accommodations following pediatric concussion.…”
Section: Discussionsupporting
confidence: 91%
“…Students in our study reported the most helpful accommodations to be engaging in cognitive and physical rest and having more time to complete work or a reduced workload. These findings are in agreement with a previous questionnaire-based study that found that 87% of concussed students were excused from physical activity, 87% received extensions on assignments, 84% were allowed excused absences, 84% received rest periods, 75% were able to postpone tests, 74% received extended testing time, 73% were permitted a reduced workload and 64% received accommodation for light and noise [31]. Taken together, the results of this pilot study have helped contribute to the development of an individually tailored return to learn (RTL) program at our tertiary pediatric concussion program, however future work is needed to evaluate the benefit of this RTL program in optimizing academic performance and accommodations following pediatric concussion.…”
Section: Discussionsupporting
confidence: 91%
“…11 An AT may serve as the academic point person and conduit to school professionals; however, we recommend that a school professional (eg, school counselor, school nurse) with training in academic accommodations and the response-tointervention process should implement appropriate academic adjustments. In a survey 10 of school nurses, 58% reported involvement in the return-to-learn progression, whereas 31.1% of ATs in our study reported school nurses' ability to implement academic accommodations. It is possible that school nurses employed at schools without an AT may be more involved in the return-to-learn process or that ATs may not be fully aware of school nurses' ability to implement accommodations.…”
Section: Communicating Health and Academic Progressmentioning
confidence: 56%
“…2 School nurses are often involved in the facilitation of 504 plans and have reported their involvement in monitoring adolescents' return to learn after concussion. 10 However, little is known regarding athletic trainers' (ATs') role in the return-to-learn process.…”
mentioning
confidence: 99%
“…Three of the 4 studies used a cross-sectional survey to assess the role of school nurses or athletic trainers in implementing academic accommodations in the secondary school setting. Specifi- cally, Weber et al 24 showed that 59% of student-athletes with concussions who were under the care of a school nurse received academic accommodations, whereas Olympia et al 25 demonstrated that 58% of school nurses were responsible for guiding the graduated academic-reentry process for student-athletes with concussions. Williams et al, 26 on the other hand, reported that 41% of studentathletes under the care of an athletic trainer employed in the secondary school setting received academic accommodations after a sport-related concussion.…”
Section: Use Of Restmentioning
confidence: 99%